Implementasi Manajemen Mutu Terpadu (TQM) di MTs Yathasi Kota Bogor - Gunarti Sukriyatun; Maemunah Sa’diyah (Reslaj : Religion Education Social Laa Roiba Journal, 2021)
This study aims to determine (a) the implementation of Integrated Quality Management (TQM) in YATASHI Madrasah (MTs) Bogor City (b) the results of quality report cards for YATASHI Madrasah Tsanawiyah (MTs) Bogor City. This study uses the expos faxto method from the results of the YATASHI Madrasah Tsanawiyah (MTs) performance report cards, Bogor city. The quality report card instrument is an instrument that has been standardized nationally, filled in by the Head of Madrasah, deputy head of madrasah, teachers, madrasa committee, education staff and students. The results of the Madrasah performance quality report card show that the Discipline of Madrasah Citizens has fulfilled the quality culture aspect of 93%. The self-development of teachers and education personnel is achieved at a performance level of 75% of the Quality Culture Aspect. Preparation, implementation and assessment of the perfect learning process meets the 100% performance level. The use of learning materials is achieved 95% and Financing Planning is met at a performance level of 94%. The conclusion from the Madrasah performance quality report card (YATASHI) is on average very good, but there is something that still needs to be improved, namely the education personnel development component.